Efektifitas Pembentukan Daerah Berdasarkan UU No 8 Tahun 2023 Guna Mendukung Otonomi Daerah Di Indonesia - Septian Arjuanda Putra Simatupang; Irna Sri Talenta; Helen Meliana R Hutajulu; Rizkika Kartadinata Siahaan; Sri Hadiningrum (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2024)
This research examines the effectiveness of regional formation based on Law Number 8 of 2023 in order to support regional autonomy in Indonesia. The phenomenon of large-scale regional formation is quite worrying considering that many proposals are colored by the self-interest of the local elites who support them. Regional formation has only become a commodity of "political business" by local elites. "Hijacking" or manipulation of the formation of this area ultimately gave rise to many conflicts and problems at the local level, both in the expansion area itself and in its parent area. The method used in this study is a library research method or approach. The results and discussion of the research are in accordance with the mandate of the 1945 Constitution, that Regional Governments have the authority to regulate and manage government affairs themselves according to the principles of autonomy and assistance duties. The granting of broad autonomy to regions is aimed at accelerating the realization of community welfare through improving services, empowerment and community participation.